2021
DOI: 10.1007/s10461-021-03165-4
|View full text |Cite
|
Sign up to set email alerts
|

Sólo Se Vive Una Vez: Evaluation of a Social Marketing Campaign Promoting HIV Screening and Prevention for Immigrant Latinxs

Abstract: Latinxs in the U.S. are disproportionately affected by HIV and more likely to have delayed diagnosis than their non-Latinx peers. We developed and implemented Sólo Se Vive Una Vez (You Only Live Once), the first Spanish-language campaign aimed at improving HIV testing and prevention among Latinx immigrants in Baltimore, Maryland. Sólo Se Vive Una Vez featured a website (www.solovive.org) and social marketing campaign promoting free HIV testing through the Baltimore City Health Department (BCHD) clinic and Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Findings from the current survey and the broader Vive evaluation demonstrate that the campaign reached a considerable fraction of the Latino community and promoted HIV testing among this group [ 27 , 28 ]. However, respondents in the post- Vive campaign period showed more stigmatizing beliefs than those surveyed pre- Vive .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the current survey and the broader Vive evaluation demonstrate that the campaign reached a considerable fraction of the Latino community and promoted HIV testing among this group [ 27 , 28 ]. However, respondents in the post- Vive campaign period showed more stigmatizing beliefs than those surveyed pre- Vive .…”
Section: Discussionmentioning
confidence: 99%
“…Social marketing has been shown to be an effective strategy for promoting HIV screening and reducing HIV stigma [ 23 , 24 ]. To improve HIV testing and linkage to care among Latinos in Baltimore, a new immigrant receiving community with a rapidly growing immigrant population, we developed the multilevel social marketing campaign Sólo Se Vive Una Vez (You Only Live Once, henceforth referred to as Vive ) through partnerships with the Baltimore City Health Department (BCHD) Latino outreach team, community members and leaders, Altavista Studios, Maryland Institute College of Art (MICA), and academic investigators from Johns Hopkins University [ 25 28 ]. The individual-level component of the campaign was a website ( www.solovive.org ) with culturally sensitive video modules which individuals could select based on their perceived barrier(s) to HIV testing and/or HIV-related stigmatizing beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 While an HIV testing campaign designed to promote testing to foreign-born Latinx individuals in Baltimore, Maryland, was not associated with increased HIV testing, it did appear to reach persons at an elevated risk for acquiring HIV/AIDS and it was connected to increases in PrEP referrals. 11 Another study found evidence that a media campaign targeting NYC-based men who have sex with men was successful at increasing PEP requests at the clinic associated with the campaign. 12 Although we found no study to demonstrate a connection between PrEP awareness campaigns and actual increases in PrEP uptake, a few studies provided support that public messaging can increase awareness of PrEP.…”
mentioning
confidence: 99%
“…Improvements in attitudes and self-efficacy toward HIV testing, as well as increased HIV testing, were connected to a 16-week campaign targeted to Latinx men having male-to-male sexual contact in Seattle 10. While an HIV testing campaign designed to promote testing to foreign-born Latinx individuals in Baltimore, Maryland, was not associated with increased HIV testing, it did appear to reach persons at an elevated risk for acquiring HIV/AIDS and it was connected to increases in PrEP referrals 11. Another study found evidence that a media campaign targeting NYC-based men who have sex with men was successful at increasing PEP requests at the clinic associated with the campaign 12.…”
mentioning
confidence: 99%